A new face of tourism: understanding preference of generation Z in Islamic tourism - Mohamed Shah, Iman Nadheera Amani; Md Sawari, Siti Salwa; Alam, Azhar; Abas, Siti Aisah (KSTCL Press, 2024)
Purpose: To determine the generation Z preference on the Islamic destination’s attribute.